Physicochemical properties and characterization of honey produced by Apis Cerana coupled with chemometrics analysis in Sabah - Lim, Robin Ah Hee (2023)
Quality and originality of honey sources often become a concern for consumers when purchasing. This study aims to characterize honey produced by honeybee (Apis cerana) in Sabah, Malaysia and other honey available in Sabah’s market - contract beekeepers (CB), unknown source (UNS), and branded honey (BH). Specifically, this study intent (i) to determine the physicochemical and biochemical properties of honey, (ii) to ascertain the mineral and heavy metal contents in honey, and (iii) to conduct chemotaxonomy on honey. Honey samples from the Rural Development Corporation (Sabah) CB were collected in the field, while honeys from UNS were purchased from vendors. Branded honeys were purchased from local supermarkets across the state of Sabah. The honey was collected from July 2018 to November 2018. Chemical characteristics of honey were evaluated from established methods and mineral contents in the honey were determined using inductively coupled plasma optical emission spectroscopy. Ultra-high-performance liquid chromatography – quadrupole time of flight mass spectrometry–based metabolomics approach was used to conduct the chemotaxonomy on honey. Significant differences were observed between sources on pH, ash content, total sugar content (TSC), electrical conductivity (EC), optical density (OD), colour intensity (CI), Pfund, proline and hydroxymethylfurfural (HMF) contents. Meanwhile, total phenolic compound (TPC), total flavonoid content (TFC), reducing sugar assay (RSA), and protein content did not show significant differences between honey sources (p > 0.05). Excluding HMF content, the TSC and ash content for all honey sources complied with Malaysia Food Act 1983, Codex Alimentarius and the EU regulations. Clear discrimination was observed on the principal component analysis (PCA) between sources using physicochemical and biochemical properties. Two factors (55.15%) are sufficient to explain the variability and importance of the honey available in Sabah: colours, EC, TFC, protein, and TPC as the first factor while the second factor is attributed by water content and TSC. Honey from contract beekeepers has the highest mineral content of K (2654 mg/kg), Ca (458 mg/kg), Mg (166 mg/kg), and Na (307 mg/kg) compared to honey sourced from UNS and BH. Presence of heavy metals (As, Cd, Pb, Zn) were detected but all were below the maximum permitted proportion according to Malaysia Food Act 1983, indicating safe for consumption or usage. Based on the chemotaxonomy analysis on the untargeted metabolomics, Hierarchical Cluster Analysis and PCA revealed clear discrimination of honey based on sources, where honeys from CB, UNS and BH were grouped differently. Partial least squares discriminant analysis showed a distinct separation of honey from CB and UNS, with 73% for explainable variation. Principle Component (PC) 1 accounted for 70.2% of the variation between the groups while PC2 accounted for 2.8% of the variation within the group in the data. Catechol is recommended as a marker to segregate authentic honey in Sabah. Sources of honey can be separated and identified using chemical methods which can explain the uniqueness of honey available in the industry of Sabah. It can be implied that honey from the contract beekeepers who reared the bees in the forest was of better quality, judging from its contents.